Crystal methamphetamine initiation among street-involved youth - Uhlmann, Sasha (2013)
BACKGROUND: Although many settings have recently documented a substantial increase in the use of methamphetamine-type stimulants, recent reviews have underscored the dearth of prospective studies that have examined risk factors associated with the initiation of crystal methamphetamine use. OBJECTIVES: Our objectives were to examine rates and risk factors for the initiation of crystal methamphetamine use in a cohort of street-involved youth. METHODS: Street-involved youth in Vancouver, Canada, were enrolled in a prospective cohort known as the At-Risk Youth Study (ARYS). A total of 205 crystal methamphetamine-naïve participants were assessed semi-annually and Cox regression analyses were used to identify factors independently associated with the initiation of crystal methamphetamine use. RESULTS: Among 205 youth prospectively followed from 2005 to 2012, the incidence density of crystal methamphetamine initiation was 12.2 per 100 person years. In Cox regression analyses, initiation of crystal methamphetamine use was independently associated with previous crack cocaine use (adjusted relative hazard [ARH] = 2.24 [95% CI: 1.20–4.20]) and recent drug dealing (ARH = 1.98 [95% CI: 1.05–3.71]). Those initiating methamphetamine were also more likely to report a recent nonfatal overdose (ARH = 3.63 [95% CI: 1.65–7.98]) and to be male (ARH = 2.12 [95% CI: 1.06–4.25]). CONCLUSIONS: We identified high rates of crystal methamphetamine initiation among this population. Males those involved in the drug trade, and those who used crack cocaine were more likely to initiate crystal methamphetamine use. Evidence-based strategies to prevent and treat crystal methamphetamine use are urgently needed.